2019
DOI: 10.1186/s40560-019-0387-z
|View full text |Cite
|
Sign up to set email alerts
|

Sepsis-associated disseminated intravascular coagulation and its differential diagnoses

Abstract: Disseminated intravascular coagulation (DIC) is a common complication in sepsis. Since DIC not only promotes organ dysfunction but also is a strong prognostic factor, its diagnosis at the earliest possible timing is important. Thrombocytopenia is often present in patients with DIC but can also occur in a number of other critical conditions. Of note, many of the rare thrombocytopenic diseases require prompt diagnoses and specific treatments. To differentiate these diseases correctly, the phenotypic expressions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 112 publications
0
32
0
6
Order By: Relevance
“…the experimental setup provided here cannot mimic the complex conditions leading to sepsis, our data give in vivo evidence that break-down of gap junctional function results in microcirculatory changes similar to those seen in sepsis (malperfusion, hypoxia) and maybe even disseminated intravascular coagulation (stasis/ thrombosis) 46. F I G U R E 5 Co-incubation with DIP abolished CBX-induced vessel diameter decrease.…”
mentioning
confidence: 69%
“…the experimental setup provided here cannot mimic the complex conditions leading to sepsis, our data give in vivo evidence that break-down of gap junctional function results in microcirculatory changes similar to those seen in sepsis (malperfusion, hypoxia) and maybe even disseminated intravascular coagulation (stasis/ thrombosis) 46. F I G U R E 5 Co-incubation with DIP abolished CBX-induced vessel diameter decrease.…”
mentioning
confidence: 69%
“…[ 18 ] reported that among children with bronchiolitis, elevation in platelet count (thrombocytosis) is a common presentation; however, it is not associated with disease severity or complications. On the contrary, sepsis is also defined as a critical thrombocytopenic disease in a number of studies [ 19 ]. Imani-Rastabi et al.…”
Section: Discussionmentioning
confidence: 99%
“…P-selectin also plays an important role in increasing neutrophil binding to ECs, thereby increasing neutrophil rolling while increasing expression of MAC-1 in PNCs, which increases neutrophil tethering and subsequent crawling [ 125 , 126 ]. There are other receptors involved in the process and readers interested in a more detailed consideration of this topic are referred to excellent reviews by [ 127 , 128 ].…”
Section: Activation Of Vascular Endothelial Cells Platelets and Neutmentioning
confidence: 99%